Chinese urbanites and the preservation of rare species in remote parts of the country: The example of Eaglewood - Michael Ahlheim; Oliver Frör; Gerhard Langenberger; Sonna Pelz (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2014)
Based on a Contingent Valuation study in Shanghai we assess people's willingness to contribute personally to the alleviation of environmental problems occurring in distant parts of the country. One split of our survey assessed Shanghai residents' willingness to pay for the preservation of rainforest in Yunnan, while the other split referred to the willingness to pay for the preservation of a single plant species (i.e. eaglewood) growing in this rainforest. The objectives of this study were twofold. Firstly, we wanted to find out if people living in big Chinese cities like Shanghai take an interest in the environmental problems existing in some remote parts of the country and if they are willing to contribute personally to remedy these problems. Secondly, we wanted to learn more about the motivation behind this kind of empathy, if it exists. We were especially interested in the question if this empathy refers to the specific environmental problems we addressed in our surveys or if it is motivated more by a general feeling of obligation towards environmental issues.
urn:nbn:de:bsz:100-opus-10274
Keywords: D61; Q51; Q57; 330; Eaglewood; rubber cultivation; biodiversity preservation; contingent valuation; ecosystem services; China